Central Bank Independence - Tognato, C. author. aut Link
XIII, 204 p.
Keywords: By engaging in an ethnography of the social text of German, European and USA monetary affairs, this book introduces a new analytical framework that will enable practitioners and academics, particularly within sociology, economics, political economy, and political science, to gain a clear understanding of the role of culture in central banking.